2010
DOI: 10.1109/tnsre.2010.2041593
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Analysis of Accuracy in the Identification of Motor Unit Spike Trains From High-Density Surface EMG

Abstract: The aim of this study was to compare the decomposition results obtained from high-density surface electromyography (EMG) and concurrently recorded intramuscular EMG. Surface EMG signals were recorded with electrode grids from the tibialis anterior, biceps brachii, and abductor digiti minimi muscles of twelve healthy men during isometric contractions ranging between 5% and 20% of the maximal force. Bipolar intramuscular EMG signals were recorded with pairs of wire electrodes. Surface and intramuscular EMG were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
224
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 217 publications
(242 citation statements)
references
References 21 publications
17
224
1
Order By: Relevance
“…The accuracy measure, Acc, used in our study was similar to that proposed by Holobar et al and Negro et al as the rate of agreement between two decomposition results. 24,55 Other similar accuracy measures have been used in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accuracy measure, Acc, used in our study was similar to that proposed by Holobar et al and Negro et al as the rate of agreement between two decomposition results. 24,55 Other similar accuracy measures have been used in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of each EMG signal was characterized in terms of the signal-to-interference ratio (SIR), 55 which is an estimate of the percentage of the signal energy explained by the manual decomposition results. The MDR and coefficient of inter-spike interval (ISI) variation (CoV) of each MUAP train were estimated using the algorithm described in Ref.…”
mentioning
confidence: 99%
“…However, recent attempts to harness the full spectrum of EMG signals available have shown that high density (HD) EMG can provide the full discharge patterns of active motor units [74][75][76][77], which may be a future alternative source of control.…”
Section: Surgical Methods To Improve Controlmentioning
confidence: 99%
“…The convolution kernel compensation method, introduced in Zazula (2004, 2007) and validated in numerous previous studies Holobar et al 2009Holobar et al , 2010Holobar et al , 2012Marateb et al 2011), was used to decompose the acquired EMG signals into contributions of individual motor units. Once identified, discharge times of individual motor units were dynamically tracked over the entire EMG signal, taking into account potential changes in shapes of motor unit action potentials (MUAPs), such as those caused by small arm movements and fatigue (Holobar et al , 2010(Holobar et al , 2012.…”
Section: Subjectsmentioning
confidence: 99%